Diversifikasi Pendapatan, Peran KBMI dan Usia Pada Profitabilitas Bank Yang Terdaftar di BEI Selama Pandemi - Septian Yudha Kusuma; Mirasanti Wahyuni; Rikawati Rikawati (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
The Covid-19 pandemic in Indonesia has resulted in an economic downturn in almost every corporate sector, one of the companies that has been affected is banking. The purpose of this study was to examine the effect of income diversification on bank profitability, and to examine the impact of KBMI and age as a moderating effect of income diversification on bank profitability. The number of samples that meet the criteria are 40 banks listed on the IDX during 2020 and 2021. The data analysis technique used to test the hypothesis is using Moderated Regression Analysis (MRA), by first testing normality and classic assumptions. The results of the study reveal that revenue diversification has a positive and significant effect on profitability, KBMI does not moderate the effect of revenue diversification on bank profitability, and bank age weakens the effect of bank revenue diversification on profitability. The research findings and contributions are discussed further in the article.